Study of Morphomeristic and Habitat Tempuring Fish (Puntius spp) In Bangka Island Freshwater - Andi Gustomi; Sri Dewi Dinata Putri; Sudirman Adibrata (Musamus Fisheries and Marine Journal, 2020)
This study aims to analyze the morphomeristic characteristics and habitat of Tempuring Fish (Puntius spp) in Bangka Island. The research was conducted from February to March 2020 at Bangka Island. The study used a survey method using primary and secondary data. Based on the analysis of the morphomeristic characteristics, The kind of tempuring (Puntius spp) which found in the Freshwater of Bangka Island are Puntius lineatus dan Puntius johorensis. Puntius lineatus on Bangka Island has a total body length (TL) ranging from 67.13 to 75.80 mm; head height (HD) ranges from 10 -12 mm; height (BD) ranged from 15.47-18.60 mm; dorsal fin radius (DR) D.I-II. 8-9; and lateral line (LL) scales ranging from 24-25 mm; characterized by having 5 vertical black lines on the body. Puntius johorensis has a total body length (TL) ranging from 59.60-80.67mm; head height (HD) ranged from 10.40 -16.00 mm; height (BD) ranged from 14.00-28.44 mm; dorsal fin radius (DR) D.I-II. 6-10; and lateral line (LL) scales ranging from 25-30 mm; characterized by having 6 vertical black lines on the body. Ecology of Tempuring in Bangka Island freshwater when viewed from several water quality parameters, including temperature ranges from 29-31 °C, pH 5, water transparency 0.27 - 0.36 m, flow velocity 0.03-0.06 m / s, and TSS range from 4-19.2 mg / l. This indicates that the water quality of the Tempuring Fish habitat on Bangka Island is still in a good range. Morphomeristic; Tempuring; Puntius lineatus; Puntius johorensis; Bangka Island